2017
DOI: 10.1016/j.jconrel.2017.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-based liposomes improve specific drug loading and release

Abstract: Aptamer technology has shown much promise in cancer therapeutics for its targeting abilities. However, its potential to improve drug loading and release from nanocarriers has not been thoroughly explored. In this study, we employed drug-binding aptamers to actively load drugs into liposomes. We designed a series of DNA aptamer sequences specific to doxorubicin, displaying multiple binding sites and various binding affinities. The binding ability of aptamers was preserved when incorporated into cationic liposom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…However, its potential to improve drug loading and release from nano carriers has not been thoroughly analyzed. Recently Lee JB et al have proposed a general approach for loading a large amount of thrombin proteins using DNA aptamer particles [52]; other authors, have developed a new strategy of drug-loading by designing drug specific aptamers to drive drugs into liposomes [53]. Of note, Dam et al [54] showed thatloading of G-quadruplex DNA aptamer AS1411 onto AuNPs could be tuned by manipulating the charge of the ligands and the particle surface by pH.…”
Section: Aptamer Loading and Release Of Apt Onpeg-aunps And Apt In Pementioning
confidence: 99%
“…However, its potential to improve drug loading and release from nano carriers has not been thoroughly analyzed. Recently Lee JB et al have proposed a general approach for loading a large amount of thrombin proteins using DNA aptamer particles [52]; other authors, have developed a new strategy of drug-loading by designing drug specific aptamers to drive drugs into liposomes [53]. Of note, Dam et al [54] showed thatloading of G-quadruplex DNA aptamer AS1411 onto AuNPs could be tuned by manipulating the charge of the ligands and the particle surface by pH.…”
Section: Aptamer Loading and Release Of Apt Onpeg-aunps And Apt In Pementioning
confidence: 99%
“…Aptamers' targeting abilities have been widely exploited, but its potential to improve drug loading and release from nanocarriers was thoroughly unexplored. Plourde et al hence utilized drug‐binding aptamers to load DOX into cationic liposomes and optimization of the charge and drug/aptamer ratios resulted in ≥80% encapsulation efficiency, tenfold improvement than classical passively encapsulating liposomal formulations …”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…The past few years has witnessed the great advances in the synthesis and characterization of various nanomaterials, such as dots, [17,18] gold nanomaterials, [19] hydrogel [20] carbon nanotubes [21] liposome [22] and so on. The combination of aptamers with novel nanomaterials has led to a wide applications.…”
Section: Aptamer-nanoparticles Systemsmentioning
confidence: 99%